Differential neural processing of unpleasant haptic sensations in somatic and affective partitions of the insula in non-suicidal self-injury (NSSI). Issue 3 (30th December 2015) - Bonenberger, Martina; Plener, Paul L.; Groschwitz, Rebecca C.; Grön, Georg; Abler, Birgit
Abstract: Altered perception and neural processing of pain have been observed during non-suicidal self-injury (NSSI). Evidence suggests that this phenomenon could be associated with the affective rather than the somatosensory dimension of pain. Sub-partitions of the insula have been suggested to process these different aspects differentially. In the present study, activation within the posterior, middle, and anterior partitions of the insula upon unpleasant electric stimulation was compared between subjects with a history of NSSI and healthy controls. Using functional magnetic resonance imaging (fMRI), we investigated a sample of 30 subjects, 14 of them with a lifetime history of NSSI. Unpleasant electric stimulation to the dorsum of the non-dominant hand was performed at four levels of increasing intensity. Significantly increasing posterior insula activation, which is likely to reflect the somatosensory aspects of unpleasant haptic sensations, was found upon parametrically increasing electric stimulation in both groups. By contrast, activation of the anterior insula, rather related to the more affective aspects of distressing stimuli, was significantly modulated only in the control group, but not in subjects with NSSI. These findings may support present hypotheses of altered processing of the more affective aspects of unpleasant or distressing experiences in NSSI, as a putatively relevant factor for understanding the etiology of this behavior. Highlights: Neural processing of electric stimulation was assessed in NSSI and healthy controls. Differential neural processing of pain was found in sub-partitions of the insula. NSSI and HC did not differ in neural responsiveness of the posterior insula. Anterior insula activation was modulated only in the control group, but not in NSSI.